Agonistic transitional justice: a global survey. Issue 6 (3rd June 2022) - Murphy, Emma; Walsh, Dawn
Abstract: To date, scholarship on agonism has mainly focussed on theoretical development and conceptual refinement. In keeping with the aims of this special issue, this article examines how agonism can be built into the design of peace processes. It asks whether agonistic principles are included in transitional justice mechanisms. To answer this question it develops five key indicators of agonism and creates a new data set providing a global overview of how agonism has been included in transitional justice provisions in over 630 peace agreements between 1990 and 2018. The findings show that some commitment to agonism is observed across a significant number of these agreements. The results also provide initial suggestions as to the distribution of agonistic transitional justice across dimensions of transitional justice and different peace agreements. Finally, the analysis indicates that agonistic transitional justice is frequently observed alongside provisions for mainstream transitional justice, underlining the need for further research that focuses on the implementation of these provisions in order to ascertain whether and how these different approaches operate in concert.